Population pharmacokinetics and exposure–response analyses of SAF-189s in Chinese patients with ALK+/ROS1+ non-small cell lung cancer - Liu, Yinhui; Tan, Yan; Hu, Lin; Li, Jinlong; Yang, Jiansong; Diao, Lei; Yang, Jin (Frontiers in Pharmacology, 2024)
SAF-189s is a potent ALK/ROS1 inhibitor, which is currently in clinical development to treat advanced ALK+/ROS1+ NSCLC. In this analysis, a comprehensive population pharmacokinetic (PopPK) model, as well as the exposure-response models for efficacy and safety were developed for SAF-189s integrating data from two clinical studies. A PopPK model for SAF-189s was developed using plasma concentrations collected from patients with ALK+/ROS1+ advanced NSCLC (n=299) and healthy subjects (n=24). Covariates (demographics, laboratory values, subject type, Concomitant medications) were evaluated to determine their potential influence on the between-patient variability in the PK of SAF-189s. Individual exposure values were used to investigate the relationship with efficacy endpoints (ORR, PFS, DOR) and key safety endpoints (adverse events of interest). The final PopPK model of SAF-189s was described by a one-compartment model with delayed first-order absorption and time-dependent elimination by allowing clearance to decrease stepwise over time. Age was incorporated as covariate on CL/F while prior anti-cancer therapy in ALK+ patients (ALKPOT) was incorporated on V/F. There was no apparent exposure-response relationship for any of the efficacy endpoints (ORR, PFS, DOR) at doses ranging from 80 mg to 210 mg. The relationships between exposure and safety suggested that a higher steady-state exposure appeared to be associated with more frequent incidence of hyperglycemia and proteinuria, the 210 mg dose group was less well tolerated than the other lower dose groups. PopPK and exposure–response models were developed for SAF-189s. These results demonstrate SAF-189s exposures are at the plateau of exposure-response (E-R) for efficacy. The 210 mg dose group had a significantly higher safety risk and the 160 mg dose group was well tolerated. The 160 mg QD of SAF-189s was selected as the recommended Phase III dose in ALK+ /ROS1+ or ROS1+ NSCLC patients.